Implicações extrínsecas na viabilidade de pseudomonas aeruginosa exposta à irradiação de led azul - Gomes, Victor Targino (2024)
The use of alternative microbial control methods to the traditional ones, which cause less damage to the ecosystem, is important in the contemporary world, especially when it comes to controlling biofilm formed by Pseudomonas aeruginosa. The light energy of high-power LEDs represents success in sustainability and microbial control skills. This work aimed to evaluate the effect of LED irradiation on the sessile and planktonic cell viability of wild isolates of P. aeruginosa. Analyzing the context of media and resourcefulness in the midst of available nutrients, phenotyping of biofilm formation and pyocyanin synthesis. Four wild isolates obtained from media immersed in degerming and disinfectant agents were tested, inoculated in BHI and Mineral broth, with added carbon sources. After incubation, adhesion, percentage of inhibition and sublethal injury were evaluated. Also evaluated in exposure to light energy from high-power LED for time intervals, measuring motility (Twitching, Swarming, Swimming), pyocyanin synthesis, percentage of inhibition after exposure and phenotyping by Congo red agar. The percentage of inhibition in almost all tests indicates strong adhesion and a weak percentage of inhibition, with 0% inhibition being the highest of 27.2%. Pyocyanin was synthesized in greater quantities, 12.56 μg/L by isolate 002B and 11.92 μg/L attributed to 002A after 2 hours of exposure to light irradiation emitting around 487.011 mW/cm2, as well as the three motility modalities were increased in relation to the control. A notable and accentuated damaging action on cells was observed, but with the premise of repair and mild phenotyping, referring to the subjectivity of growth in the medium. It is concluded that the action of high-power LED causes greater cell damage with shorter exposure time.